Dragons Love Tacos - Rubin, Adam 1983-; Salmieri, Daniel 1983- (New York : Dial Books for Young Readers, 2012)
Explores the love dragons have for tacos, and the dangers of feeding them anything with spicy salsa!
Keywords: Dragons -- Juvenile fiction; Tacos -- Juvenile fiction; Food habits -- Juvenile fiction; Humorous Stories; Dragons -- Fiction; Tacos -- Fiction; Food habits -- Fiction; Humorous Stories